Pengaruh Habatussauda Terhadap Produksi Asi Pada Ibu Post Partum Di UPT Puskesmas Buay Pemaca Tahun 2023 - Julia Fitri Yanti; Winarni Winarni (Pusat Riset dan Inovasi Nasional, 2023)
Background: Black cumin as one of the spices containing lactagogum. This spice in the form of black seeds has been known thousands of years ago and is widely used by the people of India, Pakistan and the Middle East to treat various kinds of diseases. to determine the effect of Habatussauda on milk production in postpartum mothers at the UPT Buay Pemaca Health Center in 2023. Methods: This study used a quasi-experimental design using the Pretest Posttest two Group Design research design for all postpartum mothers at the UPT Buay Pamaca Health Center who were born in June 2023 as many as 42 people were selected as samples with consecutive sampling technique which determined a sample of 30 people. The statistical test used was Mann Whitney. Results: All milk production before and after the intervention was given at a volume of <50 ml in 15 people (100%). In the intervention group for milk production with a volume of 50-89.9 ml, there were 11 people (73.3%) and 2 people (13.3%) in the control group. Meanwhile, in the production of breast milk with a volume of <50 ml, there were 4 people (26.7%) in the intervention group and 13 people (86.7%) in the control group. Conclusion: There is an effect of Black Seed extract on postpartum mother's milk production.